An Electrochemical and Spectroscopic Study on Re(CO)3(L)Cl in Dimethylformamide (L = 2, 2'‐Bipyridine). Issue 13 (17th February 2020) - Du, Jia‐Pei; Siewert, Inke
Abstract : Herein, we present an in‐depth study of the redox chemistry of Re(CO)3 (L)Cl (1 ) in dimethylformamide (dmf). Previous reports on 1 focused on acetonitrile (MeCN) and tetrahydrofuran (thf) as solvent, although the complex exhibits also a good activity in dmf in the electrochemical and photochemical CO2 reduction reaction. The combination of scan rate dependent CV data and IR spectroelectrochemical (IR‐SEC) experiments allows to derive a mechanistic scenario for the coupled electrochemical and chemical steps after reduction of the title compound. The relative reaction rates of competing pathways are distinctly different with regard to MeCN. The dimer [Re(CO)3 (L)]2, which is the main species after initial reduction of 1 in MeCN, is barely formed in dmf and [Re(CO)3 (L)Cl] – is stable. IR‐SEC data allowed to identify crucial intermediates alongside the reduction pathway of 1, and digital simulation of the CV data allowed to derive rate constants for the individual reaction steps. Abstract :